Supply Chain Strategy and Economic Activities in Traditional Fishing Communities of Families in Serang Regency, Indonesia - Amiruddin, Suwaib (International Journal of Supply Chain Management, 2020)
Abstract- This study encompasses the supply chain model of distribution of the fishing industry.Â A family is a place where interactions between individuals and the larger community happen. The first social interactions that children have are with their mother and other family members. This was a qualitative study using a case study approach to thoroughly understand the family-based culture of fishing families in Banten Province, Indonesia. The results of the study revealed that family-based childcare was liberal, and the children were allowed to choose their own activities. Childcare within a family whose mother worked abroad was undertaken by the father, and part of the economic needs were fulfilled by the mother. For families that had more fishing gear, some were able to give fishing equipment to their children, both married and unmarried, to help with their family's economic needs.